2001
DOI: 10.1021/ma0101862
|View full text |Cite
|
Sign up to set email alerts
|

AFM of Poly(vinyl alcohol) Crystals Next to an Inorganic Surface

Abstract: Crystallization of poly (vinyl alcohol) in the presence of an inorganic filler surface (sodium montmorillonite, MMT) was observed and compared to the crystallization of the neat polymer. For this purpose, several atomic force microscopy modes, providing spatial resolution between amorphous and crystalline polymer, are employed to observe filled and unfilled PVA films. The various AFM modes utilized are detailed, with the emphasis on how they can contrast stiff (crystalline) and softer (amorphous) domains on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
99
0
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 122 publications
(112 citation statements)
references
References 25 publications
12
99
0
1
Order By: Relevance
“…Recently, Wang et al [20,21] investigated the dielectric properties of solution intercalated polystyrene-MMT clay and poly(methyl methacrylate)-MMT clay nanocomposite films within the frequencies of 100 Hz-1 MHz and found that loading of 1 wt% MMT clay significantly reduces the ε′ values as compared to the pure polymer film, which is mainly due to reduction in the number of aligned dipolar groups in the presence of randomly distributed exfoliated clay nanoplatelets in the polymer matrix. In PVA-MMT clay nanocomposites, the intercalation of PVA in clay galleries and exfoliation of MMT clay nanoplatelets occur simultaneously [13][14][15][16][17]. The XRD, TEM and DSC studies established that in aqueous solution grown PVA-MMT clay nanocomposites up to 10 wt% MMT clay loading have well dispersed MMT nanoplatelets throughout the PVA matrix, i.e., nanocomposites formed are mostly exfoliated hybrids [14].…”
Section: Measurementsmentioning
confidence: 93%
See 3 more Smart Citations
“…Recently, Wang et al [20,21] investigated the dielectric properties of solution intercalated polystyrene-MMT clay and poly(methyl methacrylate)-MMT clay nanocomposite films within the frequencies of 100 Hz-1 MHz and found that loading of 1 wt% MMT clay significantly reduces the ε′ values as compared to the pure polymer film, which is mainly due to reduction in the number of aligned dipolar groups in the presence of randomly distributed exfoliated clay nanoplatelets in the polymer matrix. In PVA-MMT clay nanocomposites, the intercalation of PVA in clay galleries and exfoliation of MMT clay nanoplatelets occur simultaneously [13][14][15][16][17]. The XRD, TEM and DSC studies established that in aqueous solution grown PVA-MMT clay nanocomposites up to 10 wt% MMT clay loading have well dispersed MMT nanoplatelets throughout the PVA matrix, i.e., nanocomposites formed are mostly exfoliated hybrids [14].…”
Section: Measurementsmentioning
confidence: 93%
“…The anomalous decrease in the τ value of nanocomopsites above 1 wt% clay loading (Figure 3c) suggests that the mixed nanomorphology of the exfoliated clay tactoids randomly changes with the increase in MMT clay concentration in the aqueous solution grown PVA-MMT clay nanocomposite films, since the water suspended silicate layers becomes kinetically trapped by the randomly coiled and flexible PVA chains. The atomic force microscopy (AFM) of these nanocomposites also revealed that the PVA has a tendency to cover completely the tactoids, which is driven by strong specific interactions between the hydroxyl groups of PVA monomer units and the silanol groups of silicates and causes a strong wetting of PVA on the delaminated clay surfaces [15]. Table 1 shows that the values of PVA local chain relaxation process shape parameters α and β describing the broadening of the relaxation peak that varies anomalously with increase of MMT clay concentration in the PVA-MMT clay nanocomposites.…”
Section: Complex Dielectric Functionmentioning
confidence: 99%
See 2 more Smart Citations
“…[4][5][6][7][8] For the case of the single endfunctionalized polymers, bridging between nanoparticles via long-lived physisorbed configurations is not possible for weakly interacting polymers, such as polyolefins, and at best entanglement induced bridging interactions might occur. 4,9,10 The PP-g-MA based nanocomposites differ qualitatively from nanocomposites based on polymers that exhibit strong interactions with the nanoparticles, such as end-tethered polyamide-6/montmorillonite nanocomposites 4,[9][10][11][12] and poly(vinyl alcohol)/ montmorillonite nanocomposites; 13 in these latter hybrids, each monomer repeat-unit along the polymer has strong attractive interactions with the nanoparticles. For MA-treated PP, each PP-g-MA chain can have at most two terminal MA groups (i.e., MA are located at one or both chain ends, with the PP-backbone itself having no strong physisorbing sites for the nanoparticles); thus, PP-g-MA can adopt bridging conformations between filler particles and possibly stabilize the entanglement induced bridging interactions.…”
Section: Introductionmentioning
confidence: 99%